Modeling of a retarding potential analyzer and comparison with Express-A in-flight measurements - Nicolle, L.; Sarrailh, P.; Garrigues, L.; Hess, S.; Villemant, M. (Frontiers in Physics, 2022)
In-flight data from the Retarding Potential Analyzers (RPA) on the Russian geostationary telecommunication satellite Express-A #3 are used to validate electrical thruster plume simulations. The RPA placed on the solar array have made it possible to measure ion properties, current densities and energy distribution functions (IEDF), at different distances and field of view configurations with regard to the thrusters. The present work shows that the conventional probes theory used to interpret measurements is only valid if the probe is oriented toward the thruster. In most Express-A #3 measurements, this is not the case and it leads to incorrect interpretations. In this paper, a new RPA probe model is presented. It enables the physics of a tilted probe to be described more accurately, taking into account the view angle between the RPA entrance surface normal relative to the incoming flux direction, the flux direction non-aligned with the collection surface normal, the internal RPA electrical fields and masking effects due to RPA walls. This probe model is coupled with a simple model for ion transport from an electrical thruster source to the probe to allow a comparison with in-flight data. The comparison between Express-A #3 RPA collected currents and calculations from the new model discriminates true ion energy shift from probe misorientation effects. It also shows that highly tilted RPA measurements previously never interpreted can be understood and analyzed.